Effectiveness of Cultivation of Tiger Shrimp, Milk and Seaweed Using the Policultural Method: A Review - Gede Agus Pratama; Sang Ayu Made Putri Suryani; I Nengah Muliarta (Formosa Journal of Sustainable Research, 2023)
Polyculture is a cultivation method used to cultivate many fishery commodities in one area. The selection of fishery commodities for polyculture cultivation must be regulated so that there is no competition in obtaining feed. The purpose of this study was to determine the effectiveness of polyculture system cultivation (tiger shrimp, milkfish and seaweed). The method used is a literature review. The results obtained are the average quality of the waters for polyculture cultivation of 3 commodities, namely milkfish shrimp and seaweed, as follows; temperature 32.97, salinity 8.75, brightness 24.67, Ph 7.29, DO 3.57, TOM 72.27, NH3 0.24, H2S 0.05, NO2 0.3802, PO4 0.8694, alkalinity 7.33 total suspended solids 43.253. Polyculture of 3 commodities namely milkfish, shrimp and seaweed provides more effectiveness and benefits, especially in terms of production, land efficiency and water quality, this is because the three commodities above provide a mutually beneficial symbiosis